Preliminary Observation Study of Kampung Tahu in Tinalan Village, Kediri City, for Implementation of Educational Tourism Village Concept Based on Industrial Centers - ., Srikalimah; Wisnu Wardhana, Ludi; Ambarwati, Diana; Sholihin, Ustadus (KnE Social Sciences, 2020)
Kediri City is known by the name of the “Kota Tahu” because many tofu scattered craftsmen. There is a production center area know precisely in the village of Tinalan Kediri. Whose citizens produce tofu and dairy. The purpose of this research is to describe and analyze the implementation of the development of tofu village in Kelurahan Tinalan Kota Kediri become an educational tourism area to make various processed tofu. Researchers collect data in the field by acting as an active instrument. Researchers use data collection techniques through interviews, observations, Forum Group Discussion (FGD) and documentation. The data analysis used is an interactive analysis model. This study uses a qualitative descriptive approach. Analysis of data used include data reduction, data presentation, withdrawal conclusion/verification and validity of data is done with the trust test, acquisition, dependency and certainty and SWOT analysis. Data collection techniques are conducted with interviews, documentation and observations. Based on the results of the research, the development strategy can be concluded in the education tourism Kampung Tahu that promote promotion through mass media, social media and web. Building infrastructures such as providing adequate parking space, making the tourist attractions processed products know and involve the community in the management of tours. With the proper development strategy saw from increased strength and opportunities as well as minimizing weaknesses and avoiding threats, the educational tourism object of the tofu village that located in Kelurahan Tinalan subdistrict Pesantren Kediri City will be able to Compete with other attractions. Keywords: implementation of development of education tourism area, community empowerment, development strategy, SWOT analysis